Báo cáo lồng ghép vấn đề bình đẳng giới trong dự án Luật Tổ chức Tòa án nhân dân (sửa đổi) (Kèm Phụ lục) - Tòa án nhân dân tối cao (2023)
Toàn văn Báo cáo lồng ghép vấn đề bình đẳng giới trong dự án Luật Tổ chức Tòa án nhân dân (sửa đổi) (Kèm Phụ lục).